Adherencia terapéutica y objetivos glucémicos en diabéticos atendidos en el centro de salud Héroes del Cenepa - Guarnizo Arévalo, Rodrigo Jamphier (2023)
Within the control of type 2 diabetes mellitus participate enough factors such as early diagnosis, appropriate treatment of the pathology and compliance with it, as well as prevention and treat on time the possible complications. The biography reported that over half the patients globally do not have adequate adherence to treatment, negatively affecting their metabolic control. The current research aimed to determine the therapeutic adherence and glycemic targets, assess therapeutic adherence and glycemic targets after an intervention, and finally evaluate the relationship between therapeutic adherence and glycemic targets before and after a comprehensive intervention in patients with type 2 diabetes mellitus treated at the Heroes del Cenepa health center. It was established a quantitative longitudinal slice study, which conducted in the pretest and posttest, with a sample of 64 diabetic people, to whom the Morinsky-Green test was applied, in addition to the measurement of glycosylated hemoglobin. Acquiring in the pretest that 78.12% (n = 50) are not adherent to the treatment and 51.57% (n = 33) are not meeting the glycemic targets. In the posttest, 95.31% (n=61) fulfilled the treatment and 54.68% (n=35) complied with the glycemic targets. By establishing the relationship between variables before and after the intervention, it was found that this relationship is statistically significant. Concluding that education, monitoring, the use of monotherapy and the pillbox are effective to ensure adequate adherence, having a significant impact on glycemic control